A mãe do ambiente maternal no cárcere: vínculos e rupturas. - Gominho, Dorcas Luisa Barretto (2021)
This research brought to light the difficult reality of becoming a mother in a prison environment. The compulsory rupture of the mother-child relationship in view of the limited time the dyad spent in the prison, the lack of broader support were highlighted aspects. The research field is being built on the “Maternal Environment in Prison”. It was understood as the place where the plot of affections unfolds from the shared care in the cell of pregnant and puerperal women, which goes beyond the internal (physical) environment. In it there is a sisterhood that installs itself in the community of those disinherited mothers: when facing pain and helplessness and, together, these women covenant to care for each other. The research field was crossed by the issue of compulsory separation of the mother-baby dyad. The aim was to investigate the conditions of possibility of being a good enough mother in the Maternal Environment in Prison. Through a study of the concept of mother-environment, proposed by Winnicott, the unstructured interviews were analyzed, based on the triggering question: “How is the experience of becoming a mother in prison”. Psychoanalytic interpretation was the data analysis procedure. The examples of the interviews reported in this thesis suggest, in sum, that for some women motherhood was experienced in an extremely hostile environment. However, others stated that the mother-baby relationship was focused on the hope that religiosity offers. The psychic perspectives experienced in the Maternal Environment in Prison were run through by fear and helplessness in face of compulsory separation, the distancing made the mother-child link difficult. Breastfeeding was not prolonged in the construction of an affective bond between the mother and her baby, as there was no participant in the interviews who breastfed until the six-month period proposed by WHO. There was an early break that crossed the mother's emotional bond with her child. The rupture of the mother-baby relationship also brought a condition to think about motherhood in prison. Being good enough went through tragic life conditions of drug traffic. They were episodic love relationships during which they became pregnant, what made the family support network fragile, also due to the absence of the child's parent. The particular nuances of each interviewee could be pointed out by each one of them, which emerged during the researcher's clinical listening with traces of the exercise of being good enough in that Maternal Environment in Prison.